Microneedle-based interstitial fluid extraction for drug analysis: Advances, challenges, and prospects - Shuwen Ma; Jiaqi Li; Lixia Pei; Nianping Feng; Yongtai Zhang (Elsevier, 2023)
Similar to blood, interstitial fluid (ISF) contains exogenous drugs and biomarkers and may therefore substitute blood in drug analysis. However, current ISF extraction techniques require bulky instruments and are both time-consuming and complicated, which has inspired the development of viable alternatives such as those relying on skin or tissue puncturing with microneedles. Currently, microneedles are widely employed for transdermal drug delivery and have been successfully used for ISF extraction by different mechanisms to facilitate subsequent analysis. The integration of microneedles with sensors enables in situ ISF analysis and specific compound monitoring, while the integration of monitoring and delivery functions in wearable devices allows real-time dose modification. Herein, we review the progress in drug analysis based on microneedle-assisted ISF extraction and discuss the related future opportunities and challenges.